OUTPATIENT CARDIAC REHABILITATION OF PATIENTS AFTER CORONARY ARTERY REVASCULARIZATION, PROBLEMS AND PROSPECTS - M.A. Ovdii (Bogomolets National Medical University, 2017)
Summary. Ishemic heart disease (IHD) is the main cause of death in Ukraine and throughout the world. The use of progressive surgical and modern medications has provided hope for an improvement in the situation. But WHO's predictions about this problem are quite disappointing. Cardiac rehabilitation is still in the shadow of surgical and medical therapies. Aim. To assess the state of cardiac rehabilitation in the outpatient stage of patients after surgical treatment of IHD. Materials and methods. A retrospective analysis of outpatient charts of patients after surgical treatment of IHD was carried out, and rehabilitation was carried out in the regional rehabilitation center. Kiev during the period of 2011-2015. Results. During 2011-2015, 76 patients after operative treatment of IHD, including 70% (53 patients) after PCI, and 30% (23 patients) after CABG, turned to the regional rehabilitation center. Among the patients, 74% predominated,with an average age of 66.8 years and women 26%, with an average age of 64.5 years. The youngest patient was 44 years old, the oldest was 81 years old. It was found that only 46% of patients who were registered with a cardiologist during 2011-2015 underwent a course of physical rehabilitation on an outpatient basis, the remaining 54% were not physically rehabilitated. Among the examined, the mean BMI was 27.3 kg / m2, which corresponds to the excess body weight. Normal values  of BMI of 18-24 kg / m2 were observed only in 21%, overweight of BMI 25-30 kg / m2 in 57%, obesity grade I - BMI 30-35 kg / m2 in 10%, obesity grade II - BMI 35-40 Kg / m2 in 8%, obesity grade III - BMI 40-45 kg / m2 in 4%. Conclusions. The main problem of the outpatient phase of cardiac rehabilitation is that only a smaller half of the patients after the surgical treatment of IHD come to the rehabilitation department. Most patients after surgical treatment of IHD have overweight and obesity.